2022
DOI: 10.1108/gs-06-2022-0059
|View full text |Cite
|
Sign up to set email alerts
|

Grey system theory in engineering: a bibliometrics and visualization analysis

Abstract: PurposeThe year 2022 marks the 40th anniversary of the establishment of the grey system theory (GST), which has been widely applied in the engineering field. This paper aims to systematically identify the achievements, hotspots, knowledge structure and emerging trends in this field.Design/methodology/approachA bibliometrics analysis was conducted on relevant publications retrieved from Web of Science (WoS) using CiteSpace and MapEquation. A statistical analysis of the collected 3,384 papers was completed. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…(2022), the emergence and development of grey systems theory has caused innovation and progress across several research areas, including engineering (Liu et al. , 2022; Tao et al. , 2022), management, sustainable development (Hu and Liu, 2022), agricultural science (Li et al.…”
Section: Methodological Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…(2022), the emergence and development of grey systems theory has caused innovation and progress across several research areas, including engineering (Liu et al. , 2022; Tao et al. , 2022), management, sustainable development (Hu and Liu, 2022), agricultural science (Li et al.…”
Section: Methodological Proceduresmentioning
confidence: 99%
“…Given the prevalence of uncertain systems with small samples and limited information worldwide, GS 14,1 this method proves highly effective and widely applicable (Liu et al, 2022b;Prakash et al, 2023). Thus, as argued by Li et al (2022), the emergence and development of grey systems theory has caused innovation and progress across several research areas, including engineering Tao et al, 2022), management, sustainable development (Hu and Liu, 2022), agricultural science (Li et al, 2022) and many others.…”
Section: Use Of Ahp and Grey Fixed Weight Clusteringmentioning
confidence: 99%
“…It also does not require large sample data and depend on any inherent probability distribution. Excellent bibliometric Grey ordinal priority approach and visualization analyses with respect to application of grey system theory in diverse fields of science, engineering, management and healthcare can be available in Lixia et al (2019), Liu et al (2022), Tao et al (2022) and Prakash et al (2023).…”
Section: Grey Numbersmentioning
confidence: 99%
“…Also, Liu et al (2022) summarized the advances in GST research, various application achievements in the past 40 years, and the successful applications of GST in science and engineering. Tao et al (2022) examined and identified the achievements, hotspots, knowledge structure and emerging trends in the GST field.…”
Section: Grey Systems Theory (Gst)mentioning
confidence: 99%